Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm reading from 3 different sets of notes on generating functions and having a little trouble integrating their approaches.

First, I'm used to working with the following definitions:

$$c(n,k)=\binom{n}{k}=\frac{n!}{k!(n-k)!}$$ and $$D(n,k)=\binom{n-1+k}{k}=\binom{n-1+k}{n-1}$$

One set of notes says for any positive $n,k$ then $$c(-n,k)=(-1)^{k}\binom{n-1+k}{k}$$ gives the $k^{\text th}$ coefficient for $(1+x)^{-n}$

The other 2 sets give me the equation: $$\frac{1}{(1-x)^{n}}=\sum_{k=0}^\infty\binom{n-1+k}{n-1}x^k=\sum_{k=0}^\infty\binom{n-1+k}{k}x^k$$

He then goes on to say this last is the generating function for the series of negative binom coefficients and that it is exactly $D(n,k)$. How can both these be correct? Either the $k^{\text th}$ coefficient is $(-1)^{k}D(n,k)$ or it's $D(n,k)$ but how can it be both?

I'm obviously missing something trivial here I think...

share|cite|improve this question
up vote 1 down vote accepted

Silly me, it was something trivial.

In the first equation we're looking at $(1+x)^{-n}$ and in the second $(1-x)^{-n}$. If we make $x$ negative in the second equation then it's sign will alternate the same way as $(-1)^k$ in the first equation.

$$(1-(-x))^{-n}=\sum_{k=0}^\infty D(n,k)(-x)^k=\sum_{k=0}^\infty (-1)^kD(n,k)x^k$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.